Impact féministe sur l'art actuel: La Centrale à 40 ans = Feminist impact on contemporary art : La Centrale at 40 - Burisch, Nicole (La Centrale Galerie Powerhouse, 2015)
"Publication, célébrant les 40 ans d'engagement de la Centrale qui se voue au développement de l'histoire des pratiques artistiques féministes et soutient la visibilité d'artistes et d'initiatives moins ou peu représenté-es auprès des institutions culturelles établies"–Page 40.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; montréal; premier cycle; périodes historiques; québec; régions géographiques; sex1911; thématiques

Art et féminisme - Reckitt, Helena; Phelan, Peggy; Reckitt, Helena; Phelan, Peggy (Phaidon, 2011)
Depuis la fin des années 1960, le mouvement féministe a été à l'origine d'innovations, à la fois théoriques et pratiques, qui figurent parmi les plus intéressantes de l'art contemporain. Par ailleurs, certains succès politiques du mouvement féministe ont été obtenus grâce aux artistes, qui ont proposé de nouvelles manières d'envisager les domaines privé et public, l'objet de l'art et son sujet. En soulignant la différence des sexes, le courant féministe a aussi attiré l'attention sur le rôle de l'âge, de la classe sociale, de la race et de la sexualité dans la création artistique et dans sa réception. À la fois critiques et actrices du monde de l'art, les artistes féministes ont donné un nouvel élan à l'art considéré comme démarche à la fois politique et esthétique. Cet ouvrage, conçu par Helena Reckitt, présente les expériences, les idées et les démarches actuelles d'artistes majeures, et met en évidence le lien existant entre les différentes générations d'artistes. L'essai de Peggy Phelan, théoricienne de l'art et de la performance, jette un regard original sur les interprétations classiques de l'art des femmes et propose de nouvelles clés pour comprendre les rapports mouvants entre idées et idéaux du féminisme et pratiques artistiques.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques; théorie de l'art

WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis